Role of Ultrasonography (USG) in Female Subfertility - Sujeet Kumar Jain; Rajul Rastogi; Neha; Sushma Rani; Rehana Najam; Shelly Agarwal (Asian Journal of Medical Radiological Research, 2019)
Background: In modern era of conservative therapies and minimal invasive surgeries, imaging plays an important role in diagnosis, treatment and determination of prognosis of a disease. Role of ultrasonography (USG) in female subfertility has been documented in World Medical literature. Hence, in this study, we aim to determine the accuracy of USG in determining variety of causes of female subfertility using hysterolaparoscopy as a gold standard in our conditions. Subjects and Methods: One hundred and thirty females in reproductive age-group presenting with primary and secondary subfertility were included in the study. Females with primary amenorrhea were excluded from the study. All patients underwent endovaginal USG (EVS) while Color Doppler Flow Imaging (CDFI) was used whenever indicated. Imaging was done after 8th-10th day of menstrual cycle and a minimum of 3-4 days after complete cessation of menstrual blood flow. Results: USG is very accurate in detecting polycystic ovaries, leiomyoma / adenomyoma, etc with nearly 100% accuracy while has considerable limitations in tubal disease and in cases of pelvic inflammatory disease (PID) where the accuracy may fall up to 50%. Conclusion: USG should be first investigation of choice in all patients presenting with subfertility as it is highly accurate in detecting polycystic ovaries, leiomyoma, endometriosis / adenomyosis, endometrial thickening and uterine and ovarian anomalies. Further imaging, should be used reserved tool in patients with complex clinical disease showing unremarkable or non-characteristic USG.